Meritve telesnih značilnosti in gibalnih sposobnosti študentov Fakultete za strojništvo - Novak, Iztok (Šport (Ljubljana), 2019)
There are several studies, which identified the worldwide decline of physical activity among students and increase in their obesity. According to those studies there is a great chance their obesity will continue to their adulthood. At the Faculty of Mechanical Engineering of University of Ljubljana there are yearly measurements of students body characteristics and motoric abilities and a survey of their average weekly sports activities. Many students are not physically active enough, even though Physical Education is a part of the curriculum. We hope for similar measurement projects throughout the University of Ljubljana. We are hoping for a Physical Education system at the University, that will enable a healthy lifestyle for all the students.
Keywords: body abilities; Faculty of Mechanical Engeneering; Fakulteta za strojništvo; gibalne sposobnosti; motoric abilities; physical characteristics; physical education; sport education chart; students; športna vzgoja; športnovzgojni karton; študenti; telesna aktivnost; telesne značilnosti; University of Ljubljana; Univerza v Ljubljani; weekly activity